Current status and physician's attitude toward advance care planning in hospice palliative care units in Japan. Issue 1 (1st June 2011) - Kizawa, Y; Shima, Y; Tsuneto, S
Abstract : Objective: To examine the current status and physicians' attitude toward ACP in PCU in Japan. Method: We conducted a questionnaire survey and retrospective chart review of 203 certified PCU in December 2010. We received permission to perform a retrospective chart review of ACP before and during admission, and who made the decision to admit a patient into the hospice palliative care program for the last 3 patients who died before 30 November 2010 in each PCU. Physicians working in the PCU were asked to complete a questionnaire regarding their attitude toward, and practice of ACP. Main results: Among 203 PCUs contacted, 95 participated (response rate 47%). 285 patients were reviewed. The percentage of patients for whom their physicians expressed their intentions regarding implementation of CPR, mechanical ventilation, antibiotics, tube feeding, artificial hydration and Power of Attorney of health care prior to admission to PCU was 44%, 44%, 9%, 15%, 29% and 41% respectively. However during their admission this increased to 47%, 46%, 19%, 18%, 43% and 49% respectively. 70% of patients had a physician's order to implement DNAR and 44% of families consented to implementation of the DNAR order without discussing the issue with the patient. We also assessed physicians' attitudes toward and practice of ACP. Conclusions: This study will clarify the current status of and physicians' attitude toward ACP in PCU in Japan, and provide evidence of the unique cultural diversity toward end-of-life care and ACP among Japanese.